Screening UFMylation-associated genes in heart tissues of Ufm1-transgenic mice - Hu Jiajia; Yang Ziyao; Zheng Jiaqi; Chen Yanli; Zhao Xiaotao; Su Ming (BMC Cardiovascular Disorders, 2023)
Abstract UFMylation is a ubiquitination-like modification that is related to endoplasmic reticulum stress and unfolded protein response. A recent study reported that Ufl1, a key enzyme of UFMylation, protects against heart failure, indicating that UFMylation may be associated with heart function regulation. In the present study, we initially constructed a Flag-6×His-tagged Ufm1ΔSC transgenic (Tg-Ufm1) mouse model that enables UFMylation studies in vivo. Tg-Ufm1 mice showed significant activation of UFMylation in hearts. By using this model, we identified 38 potential Ufm1-binding proteins in heart tissues through LC‒MS/MS methods. We found that these proteins were associated with mitochondria, metabolism and chaperone binding. By using transcriptomic screening, we identified Tnfaip2 as a novel UFMylation-associated gene. Overexpression of Ufm1 significantly upregulated the protein expression of Tnfaip2, whereas isoproterenol treatment decreased Tnfaip2 expression in Tg-Ufm1 mice. These data may provide novel clues for UFMylation in cardiac hypertrophy.